Lipoprotein-associated phospholipase A2 and complications of diabetes mellitus: a systematic review and meta-analysis - Guo, Sujuan; Zhao, Xiaojuan (Frontiers in Endocrinology, 2026)
ObjectiveThis systematic review aimed to assess whether lipoprotein-associated phospholipase A2 (Lp-PLA2) is associated with increased risk of complications in patients with diabetes mellitus (DM).MethodsWe searched PubMed, Embase, Web of Science, and Scopus databases for studies fulfilling the inclusion criteria till 30 June 2025. The relationship between Lp-PLA2 and cardiovascular disorders (CVD), diabetic kidney disease (DKD), diabetic retinopathy (DR), diabetic neuropathy (DN), and lower extremity arterial disease (LEAD) was assessed using a qualitative and quantitative analysis.ResultsTwelve studies were included. The majority of studies were on DKD. Pooled analysis showed that high Lp-PLA2 was associated with significantly higher risk of DKD (OR: 1.01 95% CI: 1.01, 1.02 I2 = 93%) but not for CVD (OR: 1.11 95% CI: 0.97, 1.26 I2 = 88%), DN (OR: 2.02 95% CI: 0.40, 10.23 I2 = 88%) or DR (OR: 1.28 95% CI: 0.49, 3.34 I2 = 96%). Sensitivity analysis revealed non-significant results for DKD and CVD. Subgroup analysis for DKD showed that heterogeneity reduced to zero in cross-sectional studies, among those with <30% prevalence of DKD, and among those reporting adjusted data, but results also became non-significant across multiple subgroups.ConclusionsLimited evidence indicates that high Lp-PLA2 may be predictive of DKD in DM patients. However, the strength of the association is too low and the finding may not be relevant for clinical application. Lp-PLA2 was not found to predict CVD, DN, or DR, but with very scarce data. The high heterogeneity and non-significant results on sensitivity analysis limits the strength of the evidence. More robust studies are required to supplement the present evidence.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO CRD420251069254.